Implementation of Comprehensive Sexuality Education Policy in Public Elementary Schools in One District Camarines Norte, Philippines - JORVINA, SHIENNA MICHELLE; Cabate, Deevien C.; Delgaco, Wilma D. (PT. BATARI EDU CALYA, 2023)
Comprehensive sexuality education (CSE) is a curriculum that aims to teach young learners with the knowledge, skills, and attitudes to have a better view about sexuality and healthy relationships. It promotes safe, reliable, non-judgmental, and effective sexuality education by using age and developmentally appropriate information, learning strategies, teaching methods, and materials. This research determined the level of implementation of the policy aims of CSE in Labo West District and the level of knowledge of teachers on the said policy. The researchers designed questionnaire to collect these data. The aforementioned data were analyzed using weighted mean and Pearson r to establish the correlation between the two variables. The study further discusses the mechanism of the district to instill awareness on sexuality education among learners to decrease health risk behaviors among young children.